2019
DOI: 10.3390/nu11071581
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hydrogen Sulfide Donors from Allium sp. as a Nutraceutical Approach in Type 2 Diabetes Prevention and Therapy

Abstract: Type 2 diabetes mellitus (DM) is a socially relevant chronic disease with high prevalence worldwide. DM may lead to several vascular, macrovascular, and microvascular complications (cerebrovascular, coronary artery, and peripheral arterial diseases, retinopathy, neuropathy, and nephropathy), often accelerating the progression of atherosclerosis. Dietary therapy is generally considered to be the first step in the treatment of diabetic patients. Among the current therapeutic options, such as insulin therapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 202 publications
(177 reference statements)
0
26
0
1
Order By: Relevance
“…Oxidative stress is responsible for promoting diabetes and preclinical studies showed that garlic active organosulfur compounds reduced hyperglycemia via improving the antioxidant status in circulation of diabetic rats [ 106 ]. In addition, the garlic component acts as hydrogen sulfide donors which also control type 2 diabetes [ 109 ]. Recently, few meta-analyses demonstrated that garlic may decrease lipid profile and glucose parameters such as fasting blood glucose concentrations [ 110 , 111 ] and hemoglobin A1c (HbA1C) in diabetics patients [ 112 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…Oxidative stress is responsible for promoting diabetes and preclinical studies showed that garlic active organosulfur compounds reduced hyperglycemia via improving the antioxidant status in circulation of diabetic rats [ 106 ]. In addition, the garlic component acts as hydrogen sulfide donors which also control type 2 diabetes [ 109 ]. Recently, few meta-analyses demonstrated that garlic may decrease lipid profile and glucose parameters such as fasting blood glucose concentrations [ 110 , 111 ] and hemoglobin A1c (HbA1C) in diabetics patients [ 112 ].…”
Section: Clinical Trials On Garlicmentioning
confidence: 99%
“…We assumed that this non-toxic concentration may be rather negligible to increase the transketolase activity. At second, the widely researched garlic compounds having prop-2-en-1-yl moiety, as a two-edged sword, are able to attenuate the oxidative damage [29] and exert a beneficial anti-inflammatory effects as a slow H 2 S donor [42,43]. Allithiamine possesses a prop-2-en-1-yl moiety, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Dipeptidyl-peptidase-4 (DPP4) is the enzyme responsible for the rapid inactivation of the incretins GLP-1 and GIP [52]. Dipeptidyl-peptidase-4 (DPP4) inhibitors, namely, linagliptin, vildagliptin, sitagliptin, saxagliptin, and alogliptin, are once or twice-daily oral drugs which enhance endogenous effects of incretin by means of DPP4 inhibition, thus retarding incretin degradation and prolonging their circulating half-lives [46].…”
Section: Dipeptidyl-peptidase-4 (Dpp4) Inhibitorsmentioning
confidence: 99%
“…Since organosulfur compounds (OSCs) from plant extracts have shown antioxidant, blood glucose lowering, anti-inflammatory and immunomodulatory actions, they may be considered as cardioprotective in T2DM. Garlic OSCs have the interesting feature of gasotransmitter H2S production and should be incorporated in the dietary regimen of type 2 diabetic individuals [52,119]. These active ingredients are able to reduce glycemia by competition against insulin for liver insulin-inactivating sites, thus producing high levels of free insulin [52].…”
Section: Allium Cepa and Allium Sativummentioning
confidence: 99%
See 1 more Smart Citation